2011
DOI: 10.5054/tj.2011.259954
|View full text |Cite
|
Sign up to set email alerts
|

Learner Digital Stories in a Web 2.0 Age

Abstract: This article reports on a 4‐week class project in which students created Web 2.0 digital stories and shared and discussed them with their peers using VoiceThread, a digital media online tool. Participants were English language learners in an academic writing class at a major research university in the United States. Digital stories provided an interactive venue for building learner communities, fostering collaboration, engaging learners in multi‐literacies, and creating opportunities for global audience intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In addition to the improvement of writing self-efficacy, this study also indicates that DST is instrumental in improving students' reading. In sum, the studies reviewed in this section point out a positive influence of DST in learning motivation and writing efficacy among L2 learners (Alameen, 2011;Potts, 2013;Xu et al, 2011;Yoon, 2013). These findings suggest that DST can be a valid tool for educational purposes.…”
Section: Dst and Empowermentmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition to the improvement of writing self-efficacy, this study also indicates that DST is instrumental in improving students' reading. In sum, the studies reviewed in this section point out a positive influence of DST in learning motivation and writing efficacy among L2 learners (Alameen, 2011;Potts, 2013;Xu et al, 2011;Yoon, 2013). These findings suggest that DST can be a valid tool for educational purposes.…”
Section: Dst and Empowermentmentioning
confidence: 71%
“…Besides, creating digital stories not only enhances students' digital literacy but also helps them achieve school-based curriculum goals (Karakoyuna and Kuzub, 2013). Besides academic gains and strengthened digital literacy (Alameen, 2011), DST also exerted its influence on L1 and L2 language learning (Yoon, 2013;Potts et al, 2010;Xu et al, 2011). Yoon (2013) looked into how DST affected the 5th-grade ELL students' English learning and concluded that students' learning motivation and reading comprehension were improved.…”
Section: Dst and Its Educational Benefitsmentioning
confidence: 99%
“…(202). By contrast, Alameen (2011) reports that for learners of English at university in the USA using VoiceThread "Digital stories provided an interactive venue for building learner communities, fostering collaboration, engaging learners in multiliteracies, and creating opportunities for global audience interaction and feedback." (355).…”
Section: Feedback On Written Compositionsmentioning
confidence: 92%
“…"Digital storytelling changed my stereotyped impression on the way of teaching and learning completely…I had always been a reluctant student of English but this time I participated a lot and tried my best to create a better digital story with my partners … nobody wanted to lag behind during the final presentation… I felt so proud of our group when we showed the video and shared our experiences of making such an English digital story in front of the audience…what a sense of achievement!" (One of the students said in his reflective journal, Spring 2015, translated from Chinese by the author) 1 Willingness is essential and has a great influence on English as a Foreign Language (EFL) learning. As Gardner and Lambert (1972) divided motivation into two very general orientations: integrative and instrumental.…”
Section: Introductionmentioning
confidence: 99%
“…As Gardner and Lambert (1972) divided motivation into two very general orientations: integrative and instrumental. The 1 The reflective journals focused on three aspects of questions: Students' attitudes and opinions about digital storytelling, what they gained most from this new way of learning, and their suggestions. Their answers could be either in English or in Chinese for collecting more valid information.…”
Section: Introductionmentioning
confidence: 99%